Comparing Pressure Aging Vessel Time to Field Aging of Binder as a Function of Pavement Depth and Time. Issue 28 (December 2018) - Smith, Braden T.; Howard, Isaac L.; Jordan, Walter S.; Daranga, Codrin; Baumgardner, Gaylon L.
The AASHTO R28 pressure aging vessel (PAV) binder conditioning protocol has been heavily used for over two decades as part of purchasing specifications. Many paving industry changes have occurred since PAV was implemented in the early 1990s. This paper provides discussion with respect to a controlled test section in which the exact binders from construction were subjected to multiple PAV times and compared with properties observed after 2 or 4 years of field aging. The data suggests that 2 and 4 years of field aging were best simulated by 21 h and 45 h of PAV time for binders extracted from the top 1.3 cm of the pavement surface. For binders extracted from 5.0 to 6.3 cm below the pavement surface (i.e., at depth), 2 and 4 years of field aging were best simulated by 3 and 14 h of PAV conditioning, respectively. These results indicate that a PAV rate of 11 h per year of simulation seemed adequate for binders aged on the pavement surface, and a PAV rate of 3 h per year of simulation seemed most reasonable for binders aged at depth. Considering these rates, the current 20-h protocol in R28 seems to simulate roughly 2 years of aging at the pavement surface and about 6.5 years at depth. The amount of field aging simulation at depth is within the range of 5 to 10 years of aging suggested by R28.